Le zodiaque dans la décoration ecclésiale médiévale : une autre manière de penser le temps et l’espace - Angélique Ferrand (Bulletin du Centre d’Études Médiévales d’Auxerre)
The medieval Zodiac is other that these popular signs that we know nowadays. The Middle Ages and the Zodiac have in common to be perceived as familiars and strangers in the same time. Our purpose is to observe the complexity and the singularity of the Zodiac. Moreover we want also study modalities of apprehension of systems of representation of time and space in Middle Ages. The Zodiac plays the role of leitmotiv in this itinerary. This iconographic theme is presented from a historiographic point of view in order to point out what relates to a rejection or a fascination. So, we approach his connections with the theme of the Calendar and we examine the process of Zodiac Editions. Then, the matter is to consider stakes and modalities to represent temporality and spatiality in the Middle Ages through two examples of cycles of the Zodiac which are the central portal of the narthex of St. Marie-Madeleine at Vézelay and the pillar of St. Pierre of Souvigny. Finally, we observe the iconographic characteristics of the zodiacal signs which indicate an interplay of variations and continuity. A capital of Vézelay with Libra and Gemini as the instrument of the Last Judgment associated with Adam and Eve synthetizes some of ideas of this study which aims to show another face of the Zodiac.